{a(1)=−13}
{a(n)=a(n−1)+4}
Selenito:
Questão está incompleta
Respostas
respondido por:
1
a(n)=a(n-1)+4
n representa a posição, o segundo termo tem posição 2, n=2 então
a(2)=a(2-1)+4
a(2)=a(1)+4
a(2)=-13+4
a(2)=-9
n representa a posição, o segundo termo tem posição 2, n=2 então
a(2)=a(2-1)+4
a(2)=a(1)+4
a(2)=-13+4
a(2)=-9
respondido por:
0
Boa noite llary
a1 = -13
a2 = a1 + 4 = -13 + 4 = -9
a3 = a2 + 4 = -9 + 4 = -5
a4 = a3 + 4 = -5 + 4 = -1
etc
a1 = -13
a2 = a1 + 4 = -13 + 4 = -9
a3 = a2 + 4 = -9 + 4 = -5
a4 = a3 + 4 = -5 + 4 = -1
etc
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás